2021
DOI: 10.1002/ejic.202100495
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural Characterization and Antiproliferative Activity of Gold(I) and Gold(III) Complexes Bearing Thioether‐Functionalized N‐Heterocyclic Carbenes

Abstract: A series of gold(I) and gold(III) complexes with N‐heterocyclic carbene ligands functionalized with a pendant thioether group (NHC‐SR) was synthesized with straightforward procedures and characterized in solution with NMR spectroscopy and ESI‐MS spectrometry, as well as in the solid state by means of single crystal X‐ray diffraction analysis. Selected experimental aspects were rationalized through relativistic DFT calculations. The gold(I) and gold(III) complexes displayed moderate in vitro cytotoxicity toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…The most bioactive complex was 72 with an IC 50 value of 3.98 ± 0.58 μM against MCF-7 cells. 84 Longo et al reported the synthesis of N , N ′-hydroxy derivative of NHC silver and gold( i ) complexes. All complexes were characterized by spectroscopic and analytical techniques.…”
Section: Gold(i) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…The most bioactive complex was 72 with an IC 50 value of 3.98 ± 0.58 μM against MCF-7 cells. 84 Longo et al reported the synthesis of N , N ′-hydroxy derivative of NHC silver and gold( i ) complexes. All complexes were characterized by spectroscopic and analytical techniques.…”
Section: Gold(i) Complexes As Anticancer Agentsmentioning
confidence: 99%
“…It is worth mentioning that thermal and entropic corrections of the electronic energies did not have a significant impact on the relative energies ( Tables S7 and S8 ). The amplitudes of these formation energies are characteristic of comparable gold-NHC complexes reported in the literature [ 31 , 46 ]. Because the reaction for the formation of complex 4 differed from that occurring for the formation of complex 3 , we also considered the formation of a hypothetical complex [Au(C 6 F 5 ) 3 (SIPr)] ( 4* ), Scheme 3 .…”
Section: Resultsmentioning
confidence: 55%
“…However, although the S-functionalized N-heterocyclic carbenes are less represented, they are also an interesting class of ligands because they can potentially provide an “on and off” dynamic chelating effect for the metal complex during a catalytic cycle. This hemilability has been particularly demonstrated for the thioether function with different metals . NHC-SR metal complexes have demonstrated their catalytic activity in several transformations such as hydrosilylation of aldehydes and ketones, the Suzuki–Miyaura cross-coupling reaction, hydrogenation of double bonds, the click reaction, dehydrogenation of amine, and the reaction of amidation .…”
Section: Introductionmentioning
confidence: 99%
“…This hemilability has been particularly demonstrated for the thioether function with different metals. 22 NHC-SR metal complexes have demonstrated their catalytic activity in several transformations such as hydrosilylation of aldehydes 22e and ketones, 23 the Suzuki–Miyaura cross-coupling reaction, 24 hydrogenation of double bonds, 25 the click reaction, 26 dehydrogenation of amine, 27 and the reaction of amidation. 28 Only two examples were reported for NHC-SR rhodium(I) complexes by the group of Poli 22 and the group of Lassaletta, 29 and none of them were applied to cycloaddition reactions.…”
Section: Introductionmentioning
confidence: 99%